Competition between Exceptionally Long‐Range Alkyl Sidechain Ordering and Backbone Ordering in Semiconducting Polymers and Its Impact on Electronic and Optoelectronic Properties. (12th December 2018) - Carpenter, Joshua H.; Ghasemi, Masoud; Gann, Eliot; Angunawela, Indunil; Stuard, Samuel J.; Rech, Jeromy James; Ritchie, Earl; O'Connor, Brendan T.; Atkin, Joanna; You, Wei; DeLongchamp, Dean M.; Ade, Harald
Abstract: Intra‐ and intermolecular ordering greatly impacts the electronic and optoelectronic properties of semiconducting polymers. The interrelationship between ordering of alkyl sidechains and conjugated backbones has yet to be fully detailed, despite much prior effort. Here, the discovery of a highly ordered alkyl sidechain phase in six representative semiconducting polymers, determined from distinct spectroscopic and diffraction signatures, is reported. The sidechain ordering exhibits unusually large coherence lengths (≥70 nm), induces torsional/twisting backbone disorder, and results in a vertically multilayered nanostructure with ordered sidechain layers alternating with disordered backbone layers. Calorimetry and in situ variable temperature scattering measurements in a model system poly{4‐(5‐(4, 8‐bis(3‐butylnonyl)‐6‐methylbenzo[1, 2‐b:4, 5‐b′]dithiophen‐2‐yl)thiophen‐2‐yl)‐2‐(2‐butyloctyl)‐5, 6‐difluoro‐7‐(5‐methylthiophen‐2‐yl)‐2H‐benzo[d][1, 2, 3]triazole} (PBnDT‐FTAZ) clearly delineate this competition of ordering that prevents simultaneous long‐range order of both moieties. The long‐range sidechain ordering can be exploited as a transient state to fabricate PBnDT‐FTAZ films with an atypical edge‐on texture and 2.5× improved field‐effect transistor mobility. The observed influence of ordering between the moieties implies that improved molecular design can produce synergistic rather than destructive ordering effects. Given the large sidechain coherence lengths observed, such synergistic ordering should greatly improve the coherence length of backbone ordering and thereby improve electronic and optoelectronic properties such as charge transport and exciton diffusion lengths. Abstract : A crystalline alkyl sidechain phase with coherence lengths >70 nm is reported in a series of representative semiconducting polymers. This ordering induces backbone disorder, revealing competing forces of the backbone and sidechain that prevent simultaneous ordering of both the constituents. Implications for molecular design that facilitates synergistic long‐range crystallization are discussed.